Corrigendum: Polarized QED cascades (2021 New J. Phys.23 053025). (7th February 2022) - Seipt, Daniel; Ridgers, Christopher P; Del Sorbo, Dario; Thomas, Alec G R
Abstract: In the published version of the paper we made a sign error in the calculation of the direction of the magnetic field in the rest frame of the particles, which affects the definition of the spin-up direction in the collision operators. Correcting this does not affect the main claims of the paper: (i) the reduction of the cascade growth rate, (ii) the polarization of high-energy particles being opposite to Sokolov–Ternov theory, and (iii) an excess or a shortage of particle production in the early stages of cascade development in photon seeded cascades depending on the photon polarization.